Antibiotic Susceptibility Patterns of Different Uropathogenic Escherichia coli UPEC Strains at a Tertiary Care Hospital - Murugan, Sevanan (International Journal of Pharmaceutical & Biological Archive, 2012)
Antibiotic Susceptibility Patterns of Different Uropathogenic Escherichia coli UPEC Strains at a Tertiary Care Hospital